Functionalized Activated Carbon Derived from Biomass for Photocatalysis Applications Perspective - Samira Bagheri; Nurhidayatullaili Muhd Julkapli; Sharifah Bee Abd Hamid (International Journal of Photoenergy)
This review highlighted the developments of safe, effective, economic, and environmental friendly catalytic technologies to transform lignocellulosic biomass into the activated carbon (AC). In the photocatalysis applications, this AC can further be used as a support material. The limits of AC productions raised by energy assumption and product selectivity have been uplifted to develop sustainable carbon of the synthesis process, where catalytic conversion is accounted. The catalytic treatment corresponding to mild condition provided a bulk, mesoporous, and nanostructure AC materials. These characteristics of AC materials are necessary for the low energy and efficient photocatalytic system. Due to the excellent oxidizing characteristics, cheapness, and long-term stability, semiconductor materials have been used immensely in photocatalytic reactors. However, in practical, such conductors lead to problems with the separation steps and loss of photocatalytic activity. Therefore, proper attention has been given to develop supported semiconductor catalysts and certain matrixes of carbon materials such as carbon nanotubes, carbon microspheres, carbon nanofibers, carbon black, and activated carbons have been recently considered and reported. AC has been reported as a potential support in photocatalytic systems because it improves the transfer rate of the interface charge and lowers the recombination rate of holes and electrons.